Overwhelming post-splenectomy sepsis in patients with asplenia and hyposplenia: a retrospective cohort study. Issue 2 (25th October 2016) - CHONG, J.; JONES, P.; SPELMAN, D.; LEDER, K.; CHENG, A. C.
SUMMARY: Overwhelming post-splenectomy infection (OPSI) is a serious complication of asplenia and is associated with encapsulated organisms, most commonly Streptococcus pneumoniae, but also Haemophilus influenzae and Neisseria meningitidis. We aimed to estimate the risk of infection in this patient group. We reviewed data collected by the Victorian Spleen Registry in Australia. On registration, all patients are asked about significant infections requiring admission to hospital for intravenous antibiotics; those requiring admission to ICU were defined as OPSI. In the 3274 asplenic patients registered 492 patients reported at least one episode of infection. There were 47 episodes of OPSI requiring intensive care (incidence rate 1·11/1000 patient-years). The risk of OPSI was highest in older patients, and there were no statistically significant differences in incidence by reason for splenectomy except for a higher rate in patients with medical hyposplenia. This study reinforces that post-splenectomy infection is a clinically significant but uncommon complication, and that fulminant infection requiring intensive care is a minority of all infections.